Corporate Social Responsibility Activities Factors and Their Affecting on Maintaining Customer Satisfaction and Loyalty in Hypermarket Industry in Malaysia - Kadhim, Kadhim Ghaffar; Harun, Amran; Hamawandy, Nawzad Majeed; Qader, Khowanas Saeed; Jamil, DiyarAbdulmajeed; Jalal, Farman Badran; Sorguli, Sarhang H. M. (The journal of contemporary issues in business and government, 2021)
The purpose of this paper is to contribute to knowledge on the impact of corporate social responsibility (CSR) activities (community support, environmentally friendly, sell locally produced products, treating employees) on customer satisfaction and loyalty (hypermarkets). This study aims to examine the influence of CSR on customer satisfaction and customer loyalty of Malaysian consumers and whether they consider CSR for hypermarket before making purchase decisions of the products and services. With the support of empirical evidence and rational arguments, a set of eleven (4) hypotheses were proposed for testing. A sample of 384 respondents loyal to hypermarket has been used to collect the data using a convenience sampling method. Data was collected from the hypermarket in Kuala Lumpur. Statistical analysis was done through SPSS for primary analysis and Smart PLS for analysis of the outer model and testing the relationships hypothesized. Findings revealed that all the hypotheses were significantly effective. The originality and value of this paper is the study of consumer-oriented CSR as a variable that allows competitive differentiation of the company, by improving the relationship with the consumers and the generation of satisfaction and loyalty. One of the major conclusions of the study is that CSR and can only yield optimal performance for the customer satisfaction and customer loyalty if it is combined with the knowledge, experiences, and outstanding abilities in the use CSR activities dimensions.